Hubungan Faktor Lingkungan Fisik dan Sosial Ekonomi Keluarga Terhadap Kejadian Pneumonia Pada Balita di Wilayah Kerja Puskesmas Tahtul Yaman Kota Jambi - Suryati Suryati; Nyimas Natasha; Nur Id'ys (Jurnal Daur Lingkungan, 2018)
Pneumonia in children including one cause of death in the world that is around 20 percent, or about 1.5 million children under five die each year from the disease. Each year there are an estimated 11-20 million children in the world were hospitalized because of pneumonia. In Indonesia, pneumonia is the leading cause of death of 13.2 percent of children under five and 12.7 percent the cause of death of children. The purpose of this study to determine the relationship between the physical environment and socio-economic families with the incidence of pneumonia in children under five in Public Health Center Tahtul Yaman Jambi City period 2015. This study is a case-control study. Retrieved 35 mothers who have children suffering from pneumonia as a case (case) and 35 mothers who have children do not suffer from pneumonia as control (control) so that the total sample of 70 respondents. The research took place in November 2016. Data was analyzed by univariate and bivariate statistical test Chi Square. Results of univariate analysis showed that patients with pneumonia mostly toddlers aged 12-23 as much as 57.1%, and pneumonia mostly male sex as much as 74.3%. The physical environment pneumonia generally unfavorable 68.6%, and a good physical environment 31.4%, the results of socioeconomic level are generally relatively high 54.3%. There is a relationship between physical environmental factors in infants, with a p-value = 0.017 and OR = 3.692 and socio-economic factors with p-value = 0.009 and OR = 5.053 with pneumonia. There is a relationship between physical environmental factors and socioeconomic families with the incidence of pneumonia in infants.